HUBUNGAN OBESITAS DENGAN CITRA DIRI DAN HARGA DIRI PADA WARGA DI DESA GAJAHWONGAN CANDEN SAMBI BOYOLALI - Endang Dwi Ningsih; Aan Jana (KOSALA : Jurnal Ilmu Kesehatan, 2016)
AbstractOverwight and obesity could be defined as over accumulation of the human bodyfat. Fatover accumulation could be more than 50% than total of bodyweight is consequency inseriouse patologies happened. When growing old, it is declining normally the bodymetabolism and cause the bodyfat storing. Personal views and attitude to effects infeeding. In every person feeding could be effected by some conditions as mood, mentally,personality, self esteem and body image, perseption in bodyshape that be affected byculture, external factors and social context in attitude towards feeding. Regarding of thebackground, the researcher interested to do a study the relation of the obesity with thebody image and the self-esteem on the people of Gajahwongan Village Canden SambiBoyolali. Purpose of the study to know the relation the obesity with the body image andthe self- esteem on the people of Gajahwongan Village Canden Sambi Boyolali.Subjects the 38 obesity villager of Gajahwongan Village Canden Sambi Boyolali. Thesampling technique to be used is saturated sampling inwhich all of the population to beused as sample.The result of multivariat test by double regresi logistic test showed the Negelkerke valueR Square 34,8%. Conclusion of the Research result shows that the obesity variable beaffected by 34,8% variable of the body image and the self-esteem and the rest balance65,2% variable be affected by external of research.Keywords: Obesity, Body Image and Self-Esteem